Peran Advokat Dalam Menghadapi Masalah Mafia Peradilan di Indonesia - Nurhidayah Hasibuan; Rina Siswi Utami; Fatimah Zahara (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The role of an Advocate as a law enforcer who is free and independent guaranteed by laws and regulations becomes very important in the law enforcement process. Based on the Advocate Law, one form of legal services provided by advocates is legal aid (Article 1 point 2 of the Advocate Law). The approach used in this study is normative juridical. In accordance with the normative juridical approach, the source of data in this study is only secondary data, in the form of primary, secondary and tertiary legal materials. The analysis used in this research is descriptive qualitative. The problem to be discussed is whether the existence of the judicial mafia disrupts the credibility of advocates or is it running as it should. From the result of the study that with the presense of the judicial mafia the credibility of advocates is dispruted. Keywords: advocate role, judicial mafia